Meta analisis pengembangan media pembelajaran game edukasi biologi berbasis soal HOTS (Higher Order Thinking Skill) terhadap literasi sains siswa SMA - Lilis Karlina; Zaenal Abidin (Jurnal Ilmiah Wahana Pendidikan, 2022)
Learning media is an important thing that is needed by teachers and students in the learning process which is expected to be student-centered active learning. The development of the 21st century has had a huge impact on student learning activities. However, students are required to have higher-order thinking skills. Students today, students have high thinking skills that are still low. Evaluation is an indicator for teachers to see the quality of learning that occurs in the classroom. This study uses the meta-analysis method, at this early stage by formulating the problem, then tracing some relevant research results to be analyzed and drawing conclusions from the research results. This study aims to determine the feasibility of learning media based on HOTS questions (Higher order thinking skills) on students' scientific literacy on biology material by analyzing literature review. Scientific articles used in this study with a sample of 20 scientific articles from 15 international journals, 5 nationally accredited journals. The technique of presenting data is using a table listing of scientific publication articles that will be analyzed into research data. The data analysis technique was carried out descriptively by analyzing and identifying scientific articles so as to produce a more informative summary. From the results of the meta-analysis that has been carried out by the author, it can be concluded that the use of learning media for biology education games based on HOTS (HIGHER ORDER THINKING SKILL) on students' scientific literacy has an effect